Efeitos da radiação ionizante na maturação de oócitos bovinos: busca por modelos de estudo em radiobiologia - Rovani, Bruno Tomazele (2015)
The medical application of ionizing radiation in radiotherapy has been crucial in the treatment of cancer due to its harmful action tumor cells, by direct interaction with DNA molecules or indirectly with the H2O molecules (radiolysis, producing Free Radicals and Reactive Oxygen Species). Both interactions may cause genetic mutations in DNA breakage and physical structure, inducing cell death. However, as a result of radiotherapy, damage to the healthy cells can occur. Women treated with irradiation abdominal, pelvic or total body irradiation, may present permanent damage and loss of ovarian primordial follicles, resulting in uterine dysfunction, premature menopause, miscarriage and infertility. In order to investigate the possible damage and consequences to the healthy cells generated by radiotherapy, in this study bovine ovaries were irradiated, which are considered a good model to study reproductive events in women. In a first experiment, after irradiation of the ovaries (dose 0,9Gy, 1,8Gy, and 3,6Gy 18,6Gy), oocytes were selected and grown for 24 hours at which time analysis of nuclear maturation were conducted. In a second experiment, after irradiation of the ovaries (1,8Gy and 18,6Gy), oocytes were selected and cultivated for 1h, at which time we assessed the frequency of DNA damage by Immunofluorescence detection of phosphorylated histone H2AX (γH2AX). At the same time (1h) cumulus cells were separated for expression analysis of genes involved in DNA repair mechanisms (53BP1, RAD52, ATM, Ku70 and Ku80), apoptosis (BAX) and cell cycle control (CCND2) through RNA extraction and qRT-PCR. Results showed that radiation doses tested did not affect the nuclear maturation rate and it was not possible to detect DNA damage by the presence histone γH2AX. All analyzed genes were expressed but IR only altered the mRNA abundance of: RAD52, BAX and CCND2. We conclude that the assessed radiation doses did not affect the evolution of the maturation process in oocytes obtained from antral follicles. However, the effects of IR in preantral follicles remains unknown.